Effects of Various Work-to-rest Ratios during High-intensity Interval Training on Athletic Performance in Adolescents - Seo, Myong-Won; Lee, Jung-Min; Jung, Hyun Chul; Jung, Sung Woo; Song, Jong Kook (International Journal of Sports Medicine, 2019)
To examine the effect of high-intensity interval training (HIIT) with different work-to-rest ratios on athletic performance in athletes. Forty-seven male Taekwondo athletes (aged 15–18 yrs) were randomly assigned into 3 HIIT groups and a control group. Each group performed 6 and 8 bouts of HIIT: 1) 1:2 (30:60 s), 2) 1:4 (30:120 s), and 3) 1:8 (30:240 s) groups while the control group performed only Taekwondo training program. All HIIT groups completed 10 sessions over 4 weeks. Athletic performance tests including VO2max test, Wingate anaerobic test, vertical jump, and agility T-test were measured at both pre- and post-tests. Two-way repeated measures ANOVA were applied to examine the performance changes between protocols. VO2max improved significantly in all HIIT groups (p<0.01), and the post-hoc test indicated that the only 1:4 group showed significant improvement compared to the control group. The HIIT with 1:4 ratio showed the effective protocol for enhancing anaerobic capacity including relative peak and mean power compared to control (p<0.01). Ten sessions of HIIT involving the 1:4 group, lasting over a brief 4-week period revealed the effective protocol for enhancing both aerobic and anaerobic capacity. Our findings provide practical implications to develop a performance-enhancing program specialized for adolescent Taekwondo athletes.
Keywords: HIIT; aerobic capacity; anaerobic capacity; adolescent athletes; taekwondo